2022
DOI: 10.1515/nanoph-2021-0728
|View full text |Cite
|
Sign up to set email alerts
|

Empirical formulation of broadband complex refractive index spectra of single-chirality carbon nanotube assembly

Abstract: Assemblies of single-walled carbon nanotubes with a specific chiral structure are promising future optofunctional materials because of their strong light–matter coupling arising from sharp optical resonances of quasi-one-dimensional excitons. Their strong optical resonances, which lie in the infrared-to-visible wavelength region, can be selected by their chiralities, and this selectivity promises a wide range of applications including photonic and thermo-optic devices. However, the broadband complex optical sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In contrast, the large-chiral-angle (21,12) SWCNT has consecutive A-sites forming partially straight open tube edges (adjacent blue and red squares). This is more apparent in the schematic representation of the open tube edges as A-sites and Z-sites in the upper panel of Figure 3d.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, the large-chiral-angle (21,12) SWCNT has consecutive A-sites forming partially straight open tube edges (adjacent blue and red squares). This is more apparent in the schematic representation of the open tube edges as A-sites and Z-sites in the upper panel of Figure 3d.…”
mentioning
confidence: 79%
“…Among carbon nanotubes, single-walled carbon nanotubes (SWCNT) have excellent properties that depend on their chiral structures, which are specified by pairs of a diameter d and chiral angle θ (Figure a) or by chiral indices ( n , m ) (Figure b). Even when SWCNTs have similar diameters and chiral angles, they may be metallic ( n – m = 3 q ; q is an integer) or semiconducting ( n – m ≠ 3 q ) with different optical transition energies originating from exciton resonances. The structure-dependent narrow-window exciton resonance provides a promising application as a wavelength-selective near-infrared-to-visible photon emitter. , In addition, even the mechanical strength of SWCNTs, whose strength-to-weight ratio is among the highest among known materials, depends on the chiral structures of the SWCNTs. , The preferred structure of SWCNTs depends on the applications; thus, structure-controlled synthesis of SWCNTs has attracted attention in a wide range of scientific fields. …”
mentioning
confidence: 99%
“…37 Their optical proper-ties made them particularly appealing as opto-functional materials, which led to the observation of different physical phenomena, such as RI changes. 38 It was further reported that the RIs of individual carbon materials are affected by photon energy using a nonlinear optical device. 39 It was also reported that CQDs incorporated into polyvinyl alcohol (PVA) nanocomposites show a maximal RI of 1.84.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nanographene’s plasmon-enhanced optical response over the visible and near-infrared spectrum was shown to provide an ideal platform for the development of electrically tunable nonlinear optical nanodevices . Their optical properties made them particularly appealing as opto-functional materials, which led to the observation of different physical phenomena, such as RI changes . It was further reported that the RIs of individual carbon materials are affected by photon energy using a nonlinear optical device .…”
Section: Introductionmentioning
confidence: 99%